White Matter Lesion Volumes on 3‐T MRI in People With MS Who Had Followed a Diet and Lifestyle Program for More Than 10 Years - Jaftha, Mariaan; Robertson, Frances; van Rensburg, Susan J.; Kidd, Martin; van Toorn, Ronald; Kemp, Merlisa C.; Johannes, Clint; Moremi, Kelebogile E.; Whati, Lindiwe; Kotze, Maritha J.; Engel-Hills, Penelope (Multiple sclerosis international, 2024)
Background : Cerebral white matter lesion (WML) formation in people with multiple sclerosis (pwMS) is linked to the death of myelin‐producing oligodendrocytes. Current MS treatment strategies focus on limiting WML accumulation and disability. Using a pathology‐supported genetic testing (PSGT) program, we identified specific risk factors for MS, categorized as deficiencies and aggravators . We developed a novel clinical methodology to mitigate these risk factors, including personalized lifestyle interventions and optimization of cerebral nutrients to prevent oligodendrocyte demise and promote remyelination. Objective : To conduct a pilot case‐control study over a 10‐year period to ascertain whether the PSGT Program can reduce or prevent WML formation in pwMS. Methods : MRI was performed at baseline as well as after an interval period of at least 10 years or longer in 22 pwMS. WML volumes were determined using Sequence Adaptive Multimodal SEGmentation (SAMSEG) software, part of FreeSurfer 7.2. Other variables included age at MRI, disease duration, disability status, and medication. Results : PwMS ( n = 13) who had followed the PSGT program for more than 10 years, had significantly smaller lesion volumes (mm 3 ) compared to pwMS who did not adhere to the program ( n = 9) (4950 ± 5303 vs. 17934 ± 11139; p = 0.002). WML volumes were significantly associated ( p = 0.02) with disability (EDSS) but not with age ( p = 0.350), disease duration ( p = 0.709), or Interferon‐ β treatment ( p = 0.70). Conclusion: Dietary and lifestyle changes may lower the risk of developing cerebral WMLs in pwMS and potentially slow disease progression. Larger studies are required to confirm the effectiveness of such interventions in pwMS.